Effect of Social Support on Job Satisfaction and Organization Commitment: Employee Engagement as a Mediating Factor - Basnet, Dinesh; Gwachha, Anju; Shrestha, Bhumika (Nepal Journal of Multidisciplinary Research, 2024)
Background- The issues of job engagement, satisfaction and social support are very crucial factors in service sector as employee being a major aspect for such organization. This study aimed to examine the mediating influence of employee engagement in between social support factors and job satisfaction relationship in IT companies of Kathmandu Valley. Methods- This study followed post positivist epistemology which consists of unbiased axiology, and numerical rhetoric assumption. In this study, descriptive and casual research design has been used. Two hundred and four valid samples were used for data analysis. Hierarchical regression was used to test the mediation hypotheses. Results- Correlation analysis indicated that the relationships among perceived supervisor support, peer support, perceived organization support, job engagement, organization engagement, job satisfaction and organization commitment are statistically significant (p<.01) and the nature of the relationships are positive. Furthermore, hierarchical regression revealed that employee engagement is the significant mediator in between social support and employee outcomes; however, all the hypotheses were not neatly reproduced. Conclusion- This study suggested that support offered by colleagues, supervisor and organizational system to the employees are seems to be engaged in their work and organization that resulted commitment towards their organization and feel satisfied. Further, IT sectors could enhance organizational commitment and job satisfaction of employees by managing the support system through supervisor and peers which make them fully engaged and dedicated in their work as well. Novelty- The newness in this study is that the social support is the root cause of organizational engagement consisting of job engagement and organization engagement and it plays the major role for determining the job satisfaction and organization commitment.